Diretrizes para estruturação de plano de segurança de água para eventos extremos: secas e cheias. Estudo de caso da implantação da sala de situação da companhia de gestão dos recursos hídricos do Ceará - Timóteo, Sósthenis de Lima (2014)
A Water Safety Plan for Extreme Events - PSAEE, has the purpose of description the procedures in potentially critical situations due to the occurrence of extreme weather events (droughts and floods). Provides the developing of preventive actions and contingency plan as a way to mitigate the effects of these phenomena. Will be developed in different and complementary steps, aiming anticipation, recognition and risk assessment, identification and monitoring of vulnerable regions and the implementation of a warning network against Floods and Droughts. The present document describes guidelines for structuring a Water Safety Plan for Extreme Events, Floods and Droughts, structured in five (05) steps; 1. Preliminary Steps, 2 Diagnostic System; 3 Operational Monitoring; 4. Management Plans and 5.Validation and Verification. As a case study, the document analyzed the process of implementing the Situation Room of the Water Resources Management Company of Ceará - COGERH , also presenting some suggestion of a Work Plan for the Situation Room, which will serve as a Management Center of Extreme Hydrological Events for the State of Ceará, Brazil.